Relevansi Pemikiran Émile Durkheim terhadap Usaha Revitalisasi Gereja Protestan Masa Kini - Layantara, Jessica Novia (Veritas : Jurnal Teologi dan Pelayanan, 2020)
The Relevance of Émile Durkheim's Thoughts for Protestant Churches Revitalization Today. This paper will provide some efforts to revitalize Protestant churches today, by analyzing the critical thinking of Émile Durkheim. Durkheim's observations and critiques of Protestantism in his day will be compared to the issues faced by the Protestant church today: the individualistic lifestyle of the congregation, lack of solidarity, individual cults, lack of respect for the sacred liturgy, and church worship including holy communion, and no clear church rules. Furthermore, this paper also offers a systematic-constructive synthesis to revitalize the church, including reconfirmation of symbols, reclarification of the sacred and nonsacred, and also reformation involving new clans in the church.